Humidification of Inspired Oxygen Is Increased With Pre-nasal Cannula, Compared to Intranasal Cannula. - Dellweg, Dominic; Wenze, Markus; Hoehn, Ekkehard; Bourgund, Olaf; Haidl, Peter (Respiratory Care, 2013)
BACKGROUND: Oxygen therapy is usually combined with a humidification device, to prevent mucosal dryness. Depending on the cannula design, oxygen can be administered pre- or intranasally (administration of oxygen in front of the nasal ostia vs cannula system inside the nasal vestibulum). The impact of cannula design on intra-nasal humidity, however, has not been investigated to date. OBJECTIVE: First, to develop a system, that samples air from the nasal cavity and analyzes the humidity of these samples. Second, to investigate nasal humidity during pre-nasal and intra-nasal oxygen application, with and without humidification. METHODS: We first developed and validated a sampling and analysis system to measure humidity from air samples. By means of this system we measured inspiratory air samples from 12 subjects who received nasal oxygen with an intra-nasal and pre-nasal cannula at different flows, with and without humidification. RESULTS: The sampling and analysis system showed good correlation to a standard hygrometer within the tested humidity range (r = 0.99, P < .001). In our subjects intranasal humidity dropped significantly, from 40.3 ± 8.7% to 35.3 ± 5.8%, 32 ± 5.6%, and 29.0 ± 6.8% at flows of 1, 2, and 3 L, respectively, when oxygen was given intra-nasally without humidification (P = .001, P < .001, and P < .001, respectively). We observed no significant change in airway humidity when oxygen was given pre-nasally without humidification. With the addition of humidification we observed no significant change in humidity at any flow, and independent of pre- or intranasal oxygen administration. CONCLUSIONS: Pre-nasal administration of dry oxygen achieves levels of intranasal humidity similar to those achieved by intranasal administration in combination with a bubble through humidifier. Pre-nasal oxygen simplifies application and may reduce therapy cost.